2022
DOI: 10.3389/fpsyg.2022.896527
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Nexus Between E-Business Processes and Organizational Performance: Can Technological Opportunism Play Any Role?

Abstract: The digitization of business processes has gained much scholarly and practical attention in the recent past. To understand their effectiveness, particularly in connection to organizational performance, the current study developed and tested a comprehensive framework. Through obtaining data from 350 manufacturing businesses, the study investigated using Smart PLS3 and found a significant influence of online procurement, channel management, and service delivery capabilities on organizational performance. Further… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 60 publications
0
3
0
Order By: Relevance
“…Several previous studies have stated that information technology has a positive and significant effect on entrepreneurial behavior in online selling (Abbad, Magboul, & AlQeisi, 2021); (Gómez, Salazar, & Vargas, 2022;(Satar & Alarifi, 2022)) which will ultimately affect performance. Company (Masud, et al, 2022;(Al-Omari, et al, 2022 ). Therefore, the fourth hypothesis proposed in this study is: H 4a : Entrepreneurial behavior in online selling mediates the effect of perceived usefulness on company performance.…”
Section: The Influence Of Information Technology On Company Performan...mentioning
confidence: 91%
See 1 more Smart Citation
“…Several previous studies have stated that information technology has a positive and significant effect on entrepreneurial behavior in online selling (Abbad, Magboul, & AlQeisi, 2021); (Gómez, Salazar, & Vargas, 2022;(Satar & Alarifi, 2022)) which will ultimately affect performance. Company (Masud, et al, 2022;(Al-Omari, et al, 2022 ). Therefore, the fourth hypothesis proposed in this study is: H 4a : Entrepreneurial behavior in online selling mediates the effect of perceived usefulness on company performance.…”
Section: The Influence Of Information Technology On Company Performan...mentioning
confidence: 91%
“…Besides acceptance, entrepreneurial behaviour online selling requires embroidery business actors to carry out stages in online selling, which consist of understanding the customer, approach, needs discovery, presentation, close and follow-up ( Hanggono & Handayani, 2015;Masud, Nurfadhilah, Tijjang, & Ali, 2022;Al-Omari, AlZgool, Ahmed, Pahi, & AlMaamary, 2022). Therefore, the third hypothesis proposed in this study is: H 3 : Entrepreneurial behaviour in online selling significantly affects company performance.…”
Section: Entrepreneurial Behaviour Online Selling On Company Performancementioning
confidence: 94%
“…The optimization process in the warehouse may be broken down into two phases: first, it is important to analyze the current warehouse state, and then, it is important to provide proposals for improvement [6,7]. An extensive study of the literature has revealed that there has been a good amount of research on resource and vehicle scheduling in warehouse management and cross-dock centers focusing on minimizing the processing time [8], handling cost [9], makespan, or lead time [10] or on optimizing the internal resources like labor, space, and dock doors.…”
Section: Introductionmentioning
confidence: 99%